EXPLORING THE FACTORS OF ORGANIZATION STRUCTURE TO IMPROVE WAQF MANAGEMENT IN MALAYSIA (International Journal of Islamic Business, 2017)
Waqf is one of the Islamic financial instruments that has been proven historically in empowering Muslim society. In Malaysia, waqf is managed by the State Religious Islamic Council (SIRC) of each state as the sole trustee of waqf. Hence, this situation has resulted in different management and organization structures. This study was conducted to explore the differences in organization structure and its waqf management. In depth interviews were conducted involving 12 informants from seven waqf institutions. The findings revealed that appropriate arrangement within the organization structure can help the institution to focus on their waqf management; hence the desired performance can be achieved. Two options in changing the structure were revealed, namely internal and external re-organization. Three factors of organization structure need to be carefully examined and considered, which are organization size, professionalism and authority to execute the re-organization, both internally and externally. SIRCs have to carefully examine the number of staff needed including staff with professional background to make sure the workload can be reduced and the management can be improved. Most of the SIRCs do not have the authority to hire more staff and change their structure. External re-organization of waqf management is one of the suggestions to gain the authority.